Mechanisms of weight loss after obesity surgery - Akalestou,E; Miras,A; Rutter,G; Le,Roux C (Endrocrine Reviews, 2022)
Obesity surgery remains the most effective treatment for obesity and its complications.Weight loss was initially attributed to decreased energy absorption from the gut buthave since been linked to reduced appetitive behaviour and potentially increasedenergy expenditure. Implicated mechanisms associating rearrangement of thegastrointestinal tract with these metabolic outcomes include central appetite control,release of gut peptides, change in microbiota and bile acids. However, the exactcombination and timing of signals remain largely unknown. In this review, we surveyrecent research investigating these mechanisms, and seek to provide insights onunanswered questions over how weight loss is achieved following bariatric surgerywhich may eventually lead to safer, nonsurgical weight-loss interventions orcombinations of medications with surgery